Pengaruh Pelatihan Dan Sikap Individu Terhadap Motivasi Kerja Peserta Pendidikan Vokasi Lembaga Pendidikan Dan Pengembangan Profesi Indonesia (Lp3i) Cabang Palembang - Arubina Bangsawan; Hendra Musa; Imam Suroso; Aras Tulip; Vivin Afini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2017)
This study aims to find out how the Effects of Training and Individual Attitudes to Work Motivation of Vocational Education Participants of Lembaga Pendidikan dan Pengembangan Profesi Indonesia (LP3I) branch of Palembang. The research usesPurposive Random Sampling method. Thus, the number of samples in this study are all participants of Vocational Education LP3I BranchofPalembang those are103 people for all majors.Methods of data analysis isMultiple Linear Regression method. The results show that training and individual attitudes significantly influence to the work motivation of Vocational Education Participants LP3I branch of Palembang either partially or simultaneously. In this research, training variable is the most dominant variable affectthe work motivation of Vocational Education Participant LP3I branch of Palembang.